Neural Network Forecast for Daily Average PM10 Concentrations - OZKAN, O. (Asian Journal of Chemistry, 2009)
Over the past years, the health impact of particulate matter (PM)has become a very current subject. In the environmental sciences a lotof research effort goes towards the understanding of the particulate matterphenomenon and the ability to forecast particulate matter concentrations.The aim of the present work is to evaluate the potential of various developedartificial neural network models to provide reliable predictions ofPM10 concentrations in Kayseri. Model structure obtained from air qualitymonitoring network system performed by the Ministry of Environmentand Forestry was developed for 18 month data of Kayseri and the structurewas refined by Levenberg-Marquardt algorithm. Performance resultsof artificial neural network models was compared with multiple regressionanalysis and neural network give better predictions than multivariateregression models.